Lmo2 and Scl/Tal1 convert non-axial mesoderm into haemangioblasts which differentiate into endothelial cells in the absence of Gata1. - Gering, M; Yamada, Y; Rabbitts, T; Patient, R (2003)
The LIM domain protein Lmo2 and the basic helix-loop-helix transcription factor Scl/Tal1 are expressed in early haematopoietic and endothelial progenitors and interact with each other in haematopoietic cells. While loss-of-function studies have shown that Lmo2 and Scl/Tal1 are essential for haematopoiesis and angiogenic remodelling of the vasculature, gain-of-function studies have suggested an earlier role for Scl/Tal1 in the specification of haemangioblasts, putative bipotential precursors of blood and endothelium. In zebrafish embryos, Scl/Tal1 can induce these progenitors from early mesoderm mainly at the expense of the somitic paraxial mesoderm. We show that this restriction to the somitic paraxial mesoderm correlates well with the ability of Scl/Tal1 to induce ectopic expression of its interaction partner Lmo2. Co-injection of lmo2 mRNA with scl/tal1 dramatically extends its effect to head, heart, pronephros and pronephric duct mesoderm inducing early blood and endothelial genes all along the anteroposterior axis. Erythroid development, however, is expanded only into pronephric mesoderm, remaining excluded from head, heart and somitic paraxial mesoderm territories. This restriction correlates well with activation of gata1 transcription and co-injection of gata1 mRNA along with scl/tal1 and lmo2 induces erythropoiesis more broadly without ventralising or posteriorising the embryo. While no ectopic myeloid development from the Scl/Tal1-Lmo2-induced haemangioblasts was observed, a dramatic increase in the number of endothelial cells was found. These results suggest that, in the absence of inducers of erythroid or myeloid haematopoiesis, Scl/Tal1-Lmo2-induced haemangioblasts differentiate into endothelial cells.